The impact of sovereign wealth funds on global financial markets - Roland Beck; Michael Fidora (European Central Bank (ECB), 2008)
This paper analyses the impact of sovereign wealth funds (SWFs) on global financial markets. It presents back-of-the-envelope calculations which simulate the potential impact of a transfer of traditional foreign exchange reserves to SWFs on global capital flows. If SWFs behave as CAPM-type investors and thus allocate foreign assets according to market capitalisation rather than liquidity considerations, official portfolios reduce their “bias” towards the major reserve currencies. As a result, more capital flows “downhill” from rich to less wealthy economies, in line with standard neoclassical predictions. More specifically, it is found that under the assumption of SWFs investing according to market capitalisation weights, the euro area and the United States could be subject to net capital outflows while Japan and the emerging markets would attract net capital inflows. It is also shown that these findings are sensitive to alternative assumptions for the portfolio objectives of SWFs. Finally, the paper discusses whether a change in net capital flows triggered by SWFs could have an impact on stock prices and bond yields. Based on an event study approach, no evidence can be found for a stock price impact of non-commercially motivated stock sales by Norway's Government Pension Fund.
Keywords: F30; F40; G15; 330; Sovereign wealth funds; capital flows; foreign exchange reserves; financial markets.; Staatsfonds; Internationaler Finanzmarkt; Kapitalmobilität; Währungsreserven; Welt